APLIKASI PATI BIJI ALPUKAT (Parcea americana. Mill) SEBAGAI EDIBLE COATING BUAH STRAWBERRY (Fragaria sp.) DENGAN PENAMBAHAN EKSTRAK JAHE (Zingiber officinale. Rosc) - Muhammad Fahmi Rangkuti; Muhammad Hafiz; Irma Julyanty Munthe; Misril Fuadi (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2019)
This study aims to study edible coating avocado starch on strawberry fruit and also to know the amount of zingiber extract used in the manufacture of edible coating on avocado seeds for strawberry fruit. This study used a complete randomized design (RAL) factorial with (2) two replications. Factor I is the amount of avocado seed starch with a password (P) consisting of 4 levels: P1 = 0%, P2 = 5%, P3 = 10%, P4 = 15%. Factor II is the amount of addition of zingiber extract with a password (D) consisting of 4 levels ie D1 = 0%, D2 = 3%, D3 = 6%, D4 = 9%. Parameters observed included: weight loss, TSS, Vitamin C, Total Acid, color organoleptic test, organoleptic aroma, organoleptic flavor. The result of statistic analysis on each parameter gives the following conclusion: the amount of avocado seed concentration gives a very significant different effect on P < 0.01 level to weight shrinkage, TSS, Vitamin C, Total Acid, color organoleptic test, and organoleptic test of flavor. While at P> 0,05 level was not significant on the organoleptic test of aroma, the amount of extract of betel leaf extract had very different effects on p <0,01 to weight shrinkage, TSS, Vitamin C, Total acid, color organoleptic test, an organoleptic test of flavor. While at p> 0,05, it was not significant to an organoleptic test of aroma. And on the interaction, the amount of avocado starch concentration and the addition of zingiber extract has a very significant different effect on weight loss, Vitamin C, and total acid. And different not significant on TSS, color organoleptic test, the organoleptic test of aroma and taste organoleptic test. The best results on weight loss were P4D4 which was 0,0900%, vitamin C was P4D4 21,130 mg / 100 gr, and total P4D4 acid 2,112%.